Design against crime: a human-centred approach to designing for safety and security - Davey, Caroline L. (Design for social responsibility series, 2017)
Introducing design against crime -- Introduction -- User as victim: the dark side of design -- What is design against crime? -- Addressing crime prevention within the design process -- Safety and security: the human perspective -- Integrating crime prevention within design development -- Concept generation & design: an offender-focused perspective -- Using design to address crime and security issues -- Crime prevention policy -- Crime prevention in European urban design and planning -- The scope of design against crime delivery -- Applications and futures -- Crime victimisation: a global perspective -- The future